2021
DOI: 10.1101/2021.11.16.468804
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Type I interferon shapes brain distribution and tropism of tick-borne flavivirus

Abstract: Neurotropic virus infections cause tremendous disease burden. Methods visualizing infection in the whole brain remain unavailable which greatly impedes understanding of viral neurotropism and pathogenesis. We devised an approach to visualize the distribution of neurotropic virus infection in whole mouse brain ex vivo. Optical projection tomography (OPT) signal was coregistered with a unique magnetic resonance imaging (MRI) brain template, enabling precise anatomical mapping of viral distribution, and the effec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 99 publications
0
6
0
Order By: Relevance
“…Recent work has begun to identify host molecular pathways impacted by LGTV infection. For example, type 1 interferon signaling has been found to impact infection and antiviral immunity in the brain 15–17 and to prevent mouse‐to‐mouse transmission 18 (when it is normally transmitted by ticks 19 ). LGTV has also been found to impact universal cellular signaling pathways including the unfolded protein response, 20,21 protein kinase c, 22 and protein kinase r 23 …”
Section: Figurementioning
confidence: 99%
“…Recent work has begun to identify host molecular pathways impacted by LGTV infection. For example, type 1 interferon signaling has been found to impact infection and antiviral immunity in the brain 15–17 and to prevent mouse‐to‐mouse transmission 18 (when it is normally transmitted by ticks 19 ). LGTV has also been found to impact universal cellular signaling pathways including the unfolded protein response, 20,21 protein kinase c, 22 and protein kinase r 23 …”
Section: Figurementioning
confidence: 99%
“…In LGTV‐infected mice, the infection was limited to grey matter of sensory ganglia. However, whether the same is true for TBEV‐infected mice, remains to be investigated 83 . The BBB provides the controlled microenvironment that is needed for complex neural signalling and interactions in the brain, 6,84 and facilitates communication between the periphery and the CNS, mainly via cytokines 6,85 .…”
Section: Interaction Of Tick‐borne Encephalitis Virus With Human Hostsmentioning
confidence: 99%
“…Other flaviviruses have demonstrated that genetic diversity in the E and NS5 regions change the phenotype of the virus including immunogenicity and pathogenicity (27). The strain of POWV or DTV used for inoculation, route and method of inoculation and time spent replicating in the periphery could affect the clinical signs and response to infection (21,23,(28)(29)(30). This is underscored by our findings in that the vectored route of inoculation can cause a diverse set of clinical signs but ultimately be relegated to either a cortical region meningoencephalitis or involve the cerebellum and spinal cord, resulting in descending myelitis.…”
Section: Powassan Virus and Deer Tick Virus Induce Neuronal Death In ...mentioning
confidence: 99%
“…Once the integrity of the BBB has been compromised, the cellular destruction and pathology associated with TBEV infection are driven by the migration of CD8+ T-lymphocytes and NK cells (20). Besides immune-mediated neuronal destruction, neuronal demise can occur throughout the CNS with deficits related to the area in the brain damaged, as evidenced by mapping a neuronal network with brains infected by the related Langat virus (LGTV) (21). Noting the differences in CNS pathogenesis of TBFV, we describe here essential differences in the pathogenicity of POWV and DTV which are of relevance as historically they were assumed to be interchangeable, which makes these findings novel and clinically relevant.…”
Section: Introductionmentioning
confidence: 99%